Functional Metagenomic Investigations of the Human Intestinal Microbiota - Moore, Aimee M.; Munck, Christian; Sommer, Morten O.; Dantas, Gautam (Frontiers in Microbiology, 2011)
The human intestinal microbiota encode multiple critical functions impacting human health, including, metabolism of dietary substrate, prevention of pathogen invasion, immune system modulation, and provision of a reservoir of antibiotic resistance genes accessible to pathogens. The complexity of this microbial community, its recalcitrance to standard cultivation and the immense diversity of its encoded genes has necessitated the development of novel molecular, microbiological, and genomic tools. Functional metagenomics is one such culture-independent technique used for decades to study environmental microorganisms but relatively recently applied to the study of the human commensal microbiota. Metagenomic functional screens characterize the functional capacity of a microbial community independent of identity to known genes by subjecting the metagenome to functional assays in a genetically tractable host. Here we highlight recent work applying this technique to study the functional diversity of the intestinal microbiota, and discuss how an approach combining high-throughput sequencing, cultivation, and metagenomic functional screens can improve our understanding of interactions between this complex community and its human host.